Dietary Supplementation of Olive Mill Waste Water Polyphenols in Rabbits: Evaluation of the Potential Effects on Hepatic Apoptosis, Inflammation and Metabolism through RT-qPCR Approach - Katia Cappelli; Flavia Ferlisi; Samanta Mecocci; Margherita Maranesi; Massimo Trabalza-Marinucci; Massimo Zerani; Alessandro Dal Bosco; Gabriele Acuti (Animals, 2021)
Agro-industrial processing for the production of food or non-food products generates a wide range of by-products and residues rich in bioactive compounds including polyphenols. The concentration of these by-products is sometimes higher than in the original raw material as in the case of olive mill waste water (OMWW), one of the main by-products of olive oil extraction. Polyphenols are secondary plant metabolites that regulate the expression of specific inflammatory genes, transcriptional factors and pro/anti-apoptotic molecules, thus modulating the signaling pathways essential for cell health and homeostasis. The liver plays a key role in regulating homeostasis by responding to dietary changes in order to maintain nutritional and physiological states. In this study a nutrigenomic approach was adopted, which focuses on the effects of diet–health–gene interactions and the modulation of cellular processes, in order to evaluate the expression of the genes (AGER, BAX, COX2, IL1B, PPARA, PPARG, SIRT1, TNFA) involved in these interactions in the livers of rabbits fed with a diet supplemented with OMWW (POL) or without supplements (control, CTR). The RT-qPCR analysis showed the down-regulation of SIRT1, TNFA, AGER, BAX and PPARA transcripts in the POL group compared to the CTR group. These results show that OMWW dietary supplementation prevents cell death and tissue deterioration in rabbits.